Arterial trombosis in microcirculation after Covid 19: Case report (Research, Society and Development, 2021)
This article aims to report the case of a male patient, diagnosed with COVID-19, and subsequent presentation of microcirculatory arterial thrombosis, as well as to publicize the management of the case. A 48-year-old male patient was admitted with Severe Acute Respiratory Syndrome (SARS) after diagnosis of COVID-19, with impairment of 60% of the lungs functional capacity. After improvement of the respiratory condition, the patient started to present sudden pain in the left hand, unfixed cyanosis, slow perfusion and reactive hyperemia, however, still had palpable ulnar and radial pulse. After the physical examination, a new test for COVID-19, hemogram, leukogram, C-reactive protein, D-dimer, prothrombin time and activated partial thromboplastin time were requested. From the results of all exams, the diagnosis of thrombosis in arterial microcirculation as a result of the infection by SARS-CoV-2 was confirmed. One approach adopted was to treat the patient's circulation problems. Up to the fourth day after the start of treatment, the patient presented no complaints of pain, with improvements in the perfusion in the affected region, with a warm hand and discrete areas of necrosis in the region of the digital pulps.